Kegiatan preservasi di Perpustakaan Umum Kota Cimahi - Emilia Angelina Prameswari; Lutfi Khoerunnisa (Jurnal Informatio, 2023)
Public Library of Cimahi City is to provide information needs for the users from Cimahi City and users from other city. The Public Library of Cimahi City has collections and library equipment that must be maintained and cared for so that they are not damaged and consumed over time, as well as the building where the collections are stored. It is necessary to pay attention to the continuity of the library service. So in library activities, it is necessary to have preservation activities to maintain collections and equipment in the library. This study aims to have a comprehensive description of preservation activities at the Public Library of Cimahi City which are divided into three stages, namely preventive, curative, and restorative. The method used is descriptive qualitative, by collecting data through observation, interviews and documentation. This study uses triangulation technique to test the validity and analysis techniques of thematic data for data analysis. The informants were librarians at the Public Library of Cimahi City. The results showed that the preservation process at the Cimahi City Public Library had not been fully implemented. The Public Library of Cimahi City focuses more on preventive activities, such as installing air conditioners to maintain humidity and room temperature; installing curtains on glass windows to prevent sunlight from hitting the collection; and perform cleaning and maintenance on every element of the library. Meanwhile, curative and restorative preservation activities at the Public Library of Cimahi City are still lacking when compared to preservation standards carried out by other libraries, which have only been implemented through collection repair activities (binding, gluing and using adhesive), and room renovation. So it can be concluded that the Public Library of Cimahi City needs to pay more attention to preservation activities so that every element that supports the sustainability of the Public Library of Cimahi City can be preserved.